2001
DOI: 10.1016/s0022-2275(20)31603-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with proteoglycans enhances the sterol efflux produced by endogenous expression of macrophage apoE

Abstract: Endogenous expression of apolipoprotein (apo)Ein macrophages facilitates cholesterol efflux in the presence and absence of extracellular sterol acceptors. A proteoglycanassociated pool of apoE has also been described. The relationship between a proteoglycan-associated pool of apoE and enhanced cholesterol efflux was investigated in these studies. Inhibition of proteoglycan expression reduced cholesterol efflux from apoE-expressing cells ( J774E ؉ ) in the presence and absence of HDL, but did not do so from non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The various anti-atherogenic functions of apoE, such as facilitated remnant lipoprotein uptake by the liver , and cholesterol efflux from macrophages , , are achieved through its interaction with cell-surface GAG. Because receptor−ligand interactions at the cell surface do not occur at equilibrium, it is important to establish the kinetics of apoE−GAG association and dissociation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The various anti-atherogenic functions of apoE, such as facilitated remnant lipoprotein uptake by the liver , and cholesterol efflux from macrophages , , are achieved through its interaction with cell-surface GAG. Because receptor−ligand interactions at the cell surface do not occur at equilibrium, it is important to establish the kinetics of apoE−GAG association and dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of apoE with CS and/or DS proteoglycans is responsible for the retention of high-density lipoproteins (HDLs) on the extracellular matrix of arterial smooth muscle cells (14), and the uptake of β-very low density lipoprotein in the brain (15). In addition, apoE-mediated cholesterol efflux from macrophages is modulated by cell-surface proteoglycans (16,17). ApoE contains two independently folded functional domains; these are a 22 kDa N-terminal domain (residues 1-191) and a 10 kDa C-terminal domain (residues 216-299) linked by a hinge region (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that a significant fraction of cellular apoE in macrophages is present on the cell sur-face (17,23), and that this cell surface pool serves as the immediate precursor for secreted apoE (17). We have also shown that apoE in this cell surface pool plays a major role in facilitating the sterol efflux produced by the endogenous expression of apoE in macrophages (24). The cellular apoE measured in Fig.…”
Section: Sr-bi Reduces Macrophage Apoe Levelmentioning
confidence: 75%
“…However, the increased expression of SR-BI appeared to accelerate the degradation of newly synthesized apoE and, thereby, reduce the amount of apoE secreted from cells. We have previously shown that apoE in a macrophage cell surface pool is important for facilitating the sterol and phospholipid efflux produced by the endogenous expression of apoE (24). We, therefore, believe that the most likely mechanism for the reduced sterol efflux after increased SR-BI expression in apoE-expressing cells is the increased degradation of newly synthesized apoE leading to a reduced cell surface pool of apoE (Fig.…”
Section: Discussionmentioning
confidence: 91%